(untitled) (Islas, 2024)
Introduction: Government management is approached as a process of great complexity, demystifying the idea that in administrative and governmental matters everything is already written or said and one simply has to follow the rules or what is established, as this contradicts the real functioning of multilevel governance. Methods: Therefore, the present article adopts the method and theory of complex thinking founded by Edgar Morin and will be linked with the most updated theory on public policies, aiming to logically present the result of this linkage in governmental management. Results: The theoretical-logical analysis points out that public governance amidst the current crisis of nation-states is of high complexity, and for its success, it is essential to adopt the work through public policies in their most updated version, as it allows integrating proposals from various actors and functioning by consensus. Conclusions: Public management is complex; diversity and inequalities require a lot of work to equalize or overcome them, through the method of working through public policies involving officials, experts, and beneficiaries, proving to be the appropriate method for designing policies, aiming for fair, equitable, and sustainable development.